MAKNA IMPERATIF DALAM TINDAK TUTUR SUATU TINJAUAN PRAGMATIK - syahid, Agus (LPPM Universitas Bumigora Mataram, 2019)
This research discusses about illocution act. Illocution is an act of saying something, which is a field of study in pragmatic. According to the title of this paper, which is â€œImperative Meaning on Speech Act as A Pragmatic studyâ€ Writer is determined to do a research on how the form of the imperative meaning can be seen from the grammatical and pragmatical side, also on how is this imperative meaning being applied into a speech act on the research object. The method used in this research is analysis- descriptive method. Based on the analysis of the story Der RÃ¤uber Hotzenplotz, the writer can clearly show that imperative meaning can be expressed not only by the construction of imperative sentence but also by the construction of declarative and interrogative sentence. The results of this research show that there are four meanings of imperatives; 1) instructive meaning, 2) requisite meaning, 3) permissive meaning, and threatening meaning.